Depression accelerates gastric cancer invasion and metastasis by inducing a neuroendocrine phenotype via the catecholamine/β2‐AR/MACC1 axis - Changqie Pan; Jianhua Wu; Siting Zheng; Huiying Sun; Yisheng Fang; Zhenhua Huang; Min Shi; Li Liang; Jianping Bin; Yulin Liao; Jinzhang Chen; Wangjun Liao (Cancer Communications, 2021)
Abstract Background Depression is a common, easily ignored, accompanied disease of gastric cancer (GC) patients and is often observed with elevated plasma catecholamine levels. Depression frequently promotes GC progression and leads to poor clinical outcomes; however, the molecular mechanisms underlying depression‐induced GC progression remain poorly understood. We aimed to study the effects of depression on GC progression and explore possible mechanisms mediating the action of depression‐associated catecholamines on GC. Methods Depression states of GC patients were graded using the Patient Health Questionnaire‐9, and plasma catecholamine levels were examined by high performance liquid chromatography coupled with tandem mass spectrometry. Migrative and invasive GC cells were examined using transwell assays, and metastatic GC niches were imaged using bioluminescence technology in a depression mouse model established with chronic unpredictable mild stress. Mouse depression‐like behaviors were assessed through sucrose preference, forced swimming, and tail suspension tests. Characteristics of the neuroendocrine phenotype were observed via RT‐PCR, Western blotting, flow cytometry, and transmission electron microscopy. Results Fifty‐one GC patients (age: 53.61 ± 1.79 years; cancer duration: 3.71 ± 0.33 months; depression duration: 2.37 ± 0.38 months; male‐to‐female ratio: 1.55:1) were enrolled in the study. Depression grade was significantly higher in GC patients showing higher plasma levels of catecholamines (epinephrine: P = 0.018; noradrenaline: P = 0.009), higher oncogene metastasis‐associated in colon cancer‐1 (MACC1) level (P = 0.018), and metastasis (P < 0.001). Further, depression‐associated catecholamine specifically bound to the beta‐2 adrenergic receptor (β2‐AR) and upregulated MACC1 expression, and thus promoting neuroendocrine phenotypic transformation through direct binding between MACC1 and synaptophysin. Eventually, the neuroendocrine phenotypic transformation accelerated GC invasion in vitro and metastasis in vivo. However, β2‐AR antagonist ICI‐118,551 or MACC1 silencing effectively blocked the catecholamine‐induced neuroendocrine phenotypic transformation and eliminated depression‐enhanced GC migration and invasion. Moreover, β2‐AR blocking or MACC1 silencing prevented GC metastasis attributed to a neuroendocrine phenotype in a depression mouse model. Conclusions Catecholamine‐induced neuroendocrine phenotypes of GC cells led to depression‐accelerated GC invasion and metastasis via the β2‐AR/MACC1 axis, while β2‐AR antagonist or MACC1 silencing could reverse it, showing promising potential therapeutic strategies for improving the outcome of GC patients with comorbid depression.